European cancer mortality predictions for the year 2019 with focus on breast cancer. (19th March 2019) - Malvezzi, M; Carioli, G; Bertuccio, P; Boffetta, P; Levi, F; La Vecchia, C; Negri, E
Abstract: Background: To overcome the lag with which cancer statistics become available, we predicted numbers of deaths and rates from all cancers and selected cancer sites for 2019 in the European Union (EU). Materials and methods: We retrieved cancer death certifications and population data from the World Health Organization and Eurostat databases for 1970–2014. We obtained estimates for 2019 with a linear regression on number of deaths over the most recent trend period identified by a logarithmic Poisson joinpoint regression model. We calculated the number of avoided deaths over the period 1989–2019. Results: We estimated about 1 410 000 cancer deaths in the EU for 2019, corresponding to age-standardized rates of 130.9/100 000 men (−5.9% since 2014) and 82.9 women (−3.6%). Lung cancer trends in women are predicted to increase 4.4% between 2014 and 2019, reaching a rate of 14.8. The projected rate for breast cancer was 13.4. Favourable trends for major neoplasms are predicted to continue, except for pancreatic cancer. Trends in breast cancer mortality were favourable in all six countries considered, except Poland. The falls were largest in women 50–69 (−16.4%), i.e. the age group covered by screening, but also seen at age 20–49 (−13.8%), while more modest at age 70–79 (−6.1%). As compared to the peak rate in 1988, over 5 million cancer deaths have been avoided in the EU over the 1989–2019 period. Of these, 440 000 were breast cancer deaths. Conclusion: Between 2014 and 2019, cancer mortality will continue to fall in both sexes. Breast cancer rates will fall steadily, with about 35% decline in rates over the last three decades. This is likely due to reduced hormone replacement therapy use, improvements in screening, early diagnosis and treatment. Due to population ageing, however, the number of breast cancer deaths is not declining.